The influence of flow parameters on minimum ignition energy and quenching distance - Lefebvre, Arthur H.; Ballal, Dilip R. (Cranfield Institute of Technology, 1974)
Experiments have been carried out on the effects of pressure, velocity, mixture strength, turbulence intensity and turbulence scale on minimum ignition energy and quenching distance. Tests were conducted at room temperature in a specially designed closedcircuit tunnel in which a fan was used to drive propane/air mixtures at subatmospheric pressures through a 9 cm square working section at velocities up to 50 m/s. Perforated plates located at the upstream end of the working section provided near-isotropic turbulence in the ignition zone ranging from 1 to 22 percent in intensity, with values of turbulence scale up to 0.8 cm. Ignition was effected using capacitance sparks whose energy and duration could be varied independently.